Coastal regions of Russia: Migration attractiveness and innovation performance - Druzhinin, Alexander; Mikhaylov, Andrey; Lialina, Anna (Quaestiones Geographicae, 2021)
Coastalisation is a widely known concept that builds on the global urbanisation of the world’s marine and ocean coasts. In this paper, the degree of coastalisation of the Russian regions is analysed using a variety of parameters, including population numbers and gross regional products, indicating the accumulation of human activity in the coastal regions against the less densely populated inland territories. This research shows that coastalisation is expected to continue, making coastal regions the most attractive for international and interregional migration, hence their high innovation performance. Based on the principles of human geography, we put forward the hypothesis that Russia’s coastal territories are highly heterogeneous in their development dynamics. This study aims to test the interdependence between migration figures and innovation values across 23 regions of Russia with access to the sea. The research design comprises three stages: calculation of innovation performance, evaluation of migration flows and the building up of a typology of coastal regions. The research results reveal an increased migration attractiveness of the country’s coastal regions, with the St. Petersburg and Kaliningrad agglomerations and the Black Sea coast of the Krasnodar Krai (region) as the main attractors. Intensive innovation activity is characteristic of St. Petersburg, the northern capital of Russia, whereas peripheral regions where the extractive industries dominate (the Yamalo-Nenets Autonomous Okrug (district), Kamchatka, Krasnoyarsk and Magadan regions) demonstrate a much weaker trend towards combining innovation performance and migration attractiveness.